Characterization, immunostimulatory and antitumor activities of a β-galactoglucofurannan from cultivated Sanghuangporus vaninii under forest - Cheng, Junwen; Wang, Yanbin; Song, Jiling; Liu, Yu; Ji, Weiwei; He, Liang; Wei, Hailong; Hu, Chuanjiu; Jiang, Yihan; Xing, Yiqi; Huang, Xubo; Ding, Hongmei; et al. (Frontiers in Nutrition, 2022)
A biomacromolecule, named as β-galactoglucofurannan (SVPS2), was isolated from the cultivated parts of Sanghuangporus vaninii under the forest. Its primary and advanced structure was analyzed by a series of techniques including GC-MS, methylation, NMR, MALS as well as AFM. The results indicated that SVPS2 was a kind of 1, 5-linked β-Glucofurannan consisting of β-glucose, β-galactose and α-fucose with 23.4 KDa. It exhibited a single-stranded chain with an average height of 0.72 nm in saline solution. The immunostimulation test indicated SVPS2 could facilitate the initiation of the immune reaction and promote the secretion of cytokines in vitro. Moreover, SVPS2 could mediate the apoptosis of HT-29 cells by blocking them in S phase. Western blot assay revealed an upregulation of Bax, Cytochrome c and cleaved caspase-3 by SVPS2, accompanied by a downregulation of Bcl-2. These results collectively demonstrate that antitumor mechanism of SVPS2 may be associated with enhancing immune response and inducing apoptosis of tumor cells in vitro. Therefore, SVPS2 might be utilized as a promising therapeutic agent against colon cancer and functional food with immunomodulatory activity.